Weak and Strong Convergence of Multistep Iteration for Finite Family of Asymptotically Nonexpansive Mappings - Jung Jong Soo (SpringerOpen, 2007)
Strong and weak convergence theorems for multistep iterative scheme with errors for finite family of asymptotically nonexpansive mappings are established in Banach spaces. Our results extend and improve the corresponding results of Chidume and Ali (2007), Cho et al. (2004), Khan and Fukhar-ud-din (2005), Plubtieng et al.(2006), Xu and Noor (2002), and many others.